Dynamics of liquid nitrogen cooling process of solid surface at wetting contact coefficient. Issue 1 (November 2015) - Smakulski, P; Pietrowicz, S
Abstract: Liquid cryogens cooling by direct contact is very often used as a method for decreasing the temperature of electronic devices or equipment i.e. HTS cables. Somehow, cooldown process conducted in that way could not be optimized, because of cryogen pool boiling characteristic and low value of the heat transfer coefficient. One of the possibilities to increase the efficiency of heat transfer, as well as the efficiency of cooling itself, it is to use a spray cooling method. The paper shows dynamics analysis of liquid nitrogen cooling solid surface process. The model of heat transfer for the single droplet of liquid nitrogen, which hits on a flat and smooth surface with respect to the different Weber numbers, is shown. Temperature profiles in calculation domains are presented, as well as the required cooling time. The numerical calculations are performed for different initial and boundary conditions, to study how the wetting contact coefficient is changing, and how it contributed to heat transfer between solid and liquid cryogen.